The Role of the Class Teacher and Librarian in Emboldening Students to Reading in the First Cycle of the Basic Education Schools from their point of view - A Field Study in Lattakia City - أمون رامي; رجب رانيا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to identify the reality of the role of the class teacher and librarian in emboldening students to reading in the first cycle of the basic education schools in Lattakia city point of view, and to identify the difference in their point of view according to variables (scientific qualification and years of experience). The research used the descriptive approach, and used a questionnaire for Teachers about their role in emboldening students to reading, has been included (14) items, and questionnaire for Librarian about their role in in emboldening students to reading, has been included (16) items, then after were confirmed validity and reliability, applied to a sample of (144) teacher and (62) librarian in first cycle of basic education schools in Lattakia city for the academic year 2020/2021. The most important results of which reached the research: The role of the class teacher and librarian in emboldening students to reading - a field study in the first cycle of the basic education schools in Lattakia city was middle degree. There is difference in the Teachers point of view between the means of degrees of the class teacher sample about their role in emboldening students to reading in the first cycle of the basic education schools in Lattakia city according to (educational qualification in favor of the Education Preparation Diploma Teachers, and to years of experience between less of 5 years and more than (10) years, in favor of teachers with experience of more than (10) years, also between teachers with experience of (5 – 10) and more than (10) years in favor of more than (10) years. There is no difference in the Librarian point of view between the means of degrees of the librarian sample about their role in emboldening students to reading in the first cycle of the basic education schools in Lattakia city according to (educational qualification), while there is statistically significant difference according to variable years of experience in favor of teachers with more than (10) years